Reliability of the EasyAngle® for Assessing Hip Range of Motion in Healthy Children - Elana Duffy; Maria Wells; Alan Miller; Megan Tondra; Antonette Doty (North American Sports Medicine Institute, 2024)
# Background The use of digital goniometry has emerged as a viable alternative to universal goniometry for assessing hip range of motion (ROM). However, few studies have assessed the use of digital goniometry in pediatric populations and there are a limited number of studies that investigate any one device. The EasyAngle® is a digital goniometer that may be beneficial for use in pediatric settings as it requires only one hand to operate the device. # Purpose The purposes of this study were 1) to establish the intrarater and interrater reliability of the EasyAngle® digital goniometer in measuring hip joint ROM in healthy elementary school-aged children, and 2) to establish preliminary normative reference values for each year of age using the EasyAngle® for hip joint ROM in healthy elementary school-aged children. # Study Design Descriptive Laboratory Study # Methods Passive hip ROM (flexion, abduction, extension, internal rotation, external rotation) was measured on each leg of healthy participants using the EasyAngle®. A total of 40 hip joints were measured. Two blinded raters conducted three trials of each hip motion on both legs. Intrarater and interrater reliability of the recorded hip range of motion were calculated using intra-class correlation coefficients (ICC) (3,1). # Results Twenty healthy children were measured (age 5-10, mean = 7.40 years old, SD = 1.37, 9 males, 11 females). Mean hip ROM was reported by age. Intrarater and interrater reliability were good to excellent for all hip ROM measurements (0.81-0.97 intra rater; 0.77- 0.91 interrater). Hip flexion had the strongest intrarater (0.96, 0.97) and interrater reliability (0.91). Intrarater reliability was lowest for hip abduction for Rater 1 and hip extension for Rater 2. Interrater reliability was lowest for hip external rotation (0.78) # Conclusion The EasyAngle® is a reliable tool for assessing hip range of motion in healthy children ages 5-10. Normative hip ROM values using the EasyAngle® are available to clinicians. # Level of Evidence Level 3- Reliability study